Efektivitas Konsumsi Ekstrak Jahe Untuk Menurunkan Emesis Pada Ibu Hamil Trimester I Di Puskesmas Sukawali - Mailinda; Futriani, Elfira Sri (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: Emesis gravidarum or morning sickness is a condition of nausea which is sometimes accompanied by vomiting (frequency less than 5 times). During pregnancy, 70-85% of women experience nausea and vomiting. This study aims to determine the effect of ginger extract on reducing the frequency of nausea and vomiting in first trimester pregnant women. Methods: This research is a quasi-experimental research with a control group pre-post test design. This research will carry out initial observations on the frequency of emesis gravidarum before being given red ginger extract and after being given ginger extract in the Sukawali Community Health Center area by comparing the average frequency before and after being given red ginger extract. The sample in this study was pregnant women in the first trimester taken using a non-probability sampling technique using a purposive sampling method with a total sample of 40 pregnant women. Results: The average frequency of nausea and vomiting in the intervention group which experienced mild nausea and vomiting was 68.6% and moderate was 31.4%, while in the control group it was mild 64.6% and moderate was 35.7%. There is an effect of giving Red Ginger extract on reducing the frequency of nausea and vomiting in pregnant women in the first trimester with a p value = 0.000. Conclusion: There was a difference in the administration of ginger extract to the control group and the intervention group, the control group was given ginger extract on the first day and the 7th day while the intervention group was given ginger extract for 7 days.and There is an effect of giving red ginger extract on reducing the frequency of nausea and vomiting in pregnant women in the first trimester